Influence of arbuscular mycorrhizal consortia and phosphorus fertilization on the yield components of piquin chili - Osuna Ávila, Pedro (2026)
Introduction. The piquin chili (Capsicum annuum L. var. glabriusculum) is a wild species of red fruit found in the northern mountains of Mexico, and it is still undergoing domestication. Understanding the role of arbuscular mycorrhizal fungi and phosphorus fertilization is essential to implement sustainable production systems. Objective. To compare the influence of three consortia of arbuscular mycorrhiza and two phosphorus fertilization controls on the yield components of piquin chili. Materials and methods. The study was conducted in the summer of 2021 in Ciudad Juárez, Mexico. Three mycorrhizal consortia and two phosphorus fertilization controls were used, with twelve observations. The analyzed variables were plant height, leaf number, stem diameter, fruit number, fruit harvest weight, unitary fruit weight, and fruit phosphorus content. The experiment was conducted using a completely randomized design. Statistical analysis of the collected data was performed using SPSS version 25 with analysis of variance. A significance of 5 % was used, and the means were compared with a Tukey test. Results. The mycorrhizal consortia significantly outperformed the control plants 1 (22 mg L-1 de P) in the studied agronomic variables (number of leaves, plant height, and stem diameter) and in yield variables (number of fruits, harvest weight, and unitary fruit weight). The three consortia contributed to the yield variables similarly to the treatments fertilized with double the phosphorus dose. Conclusions. The native and commercial mycorrhizal fungi favored the evaluated yield component variables. In addition, they contributed to fruit P content similarly to phosphorus-fertilized plants.